Experimental Investigation of Indoor Thermal Comfort under Different Heating Conditions in Winter - Zhaosong Fang; Zhisheng Guo; Weibin Chen; Huijun Wu; Zhimin Zheng (Buildings, 2022)
Owing to historical reasons, only a few locations in the Guangdong province use heating to enhance interior thermal conditions. With the variation in climate and increase in people’s lifestyle requirements, winter heating has become increasingly necessary. However, a literature review revealed that only a few studies have investigated the heating requirements during winter in the Guangdong province. In this study, we compared the thermal comfort of radiant floor heating with wall-mounted air conditioner heating. A Guangzhou University climate chamber was used in several investigations. The findings revealed that the thermal neutral temperatures of radiant heating and air conditioner heating were 22.0 °C and 23.0 °C, respectively, about 1 °C variation in temperature. Additionally, in the research on thermal reactions and local skin temperature measurements, the impact of local thermal discomfort on the overall thermal experience was also considered. The findings showed a direct relationship between the local thermal discomfort caused by radiant heating and general thermal sensation. Thermal sensation of the subjects mainly originated from the lower extremities and was significantly affected by Va (air velocity). The relationship between the local thermal discomfort of convective heating and general thermal sensation was weak and mainly caused by the uneven thermal environment. Thus, in south China, for lowering energy usage, radiant floor heating should be used to create an improved indoor thermal environment in winter.